Laboratory safety of dupilumab in moderate‐to‐severe atopic dermatitis: results from three phase III trials (LIBERTY AD SOLO 1, LIBERTY AD SOLO 2, LIBERTY AD CHRONOS). (1st December 2019) - Wollenberg, A.; Beck, L.A.; Blauvelt, A.; Simpson, E.L.; Chen, Z.; Chen, Q.; Shumel, B.; Khokhar, F.A.; Hultsch, T.; Rizova, E.; Rossi, A.B.; Graham, N.M.H.; et al.
Summary: Background: Dupilumab [a monoclonal antibody blocking the shared receptor subunit for interleukin (IL)‐4 and IL‐13] is approved for patients aged ≥ 12 years with inadequately controlled, moderate‐to‐severe atopic dermatitis (AD). Dupilumab trials of up to 52 weeks demonstrated efficacy and a favourable safety profile in patients with moderate‐to‐severe AD inadequately controlled with topical medications. Objectives: To further characterize the safety of dupilumab by evaluating clinical laboratory findings from three randomized, double‐blinded, placebo‐controlled phase III trials (LIBERTY AD SOLO 1 & 2 and LIBERTY AD CHRONOS). Methods: Patients were randomized 1 : 1 : 1 (SOLO 1 & 2) or 3 : 1 : 3 (CHRONOS) for 16 and 52 weeks, respectively, to dupilumab weekly, every 2 weeks or placebo. CHRONOS patients received a standardized concomitant topical corticosteroid regimen. Laboratory outcomes were summarized descriptively in 1376 patients from SOLO 1 & 2 and 740 from CHRONOS. Results: Treatment groups had similar results in baseline laboratory parameters. Platelets and neutrophils showed mild decreases from baseline in dupilumab vs. placebo groups. Some dupilumab‐treated patients had small transient increases in eosinophils. Grade 3 eosinophilia was reported in < 1% of dupilumab‐treated and placebo‐treated patients; no adverse events were associated with eosinophilia. Lactate dehydrogenase levels decreased from baseline during dupilumab treatment in all trials. No clinically meaningful changes were observed between treatment groups in other haematology, chemistry or urinalysis parameters. Conclusions: There were no clinically important changes in routine laboratory parameters that could be attributed to dupilumab. This study supports the use of dupilumab as a systemic treatment for moderate‐to‐severe AD that does not require laboratory monitoring. What's already known about this topic? Long‐term treatment of atopic dermatitis (AD) with conventional immunosuppressive agents is limited by the risk of significant side‐effects and a need for repeated tests to monitor haematological and/or organ (e.g. liver, kidney) toxicities. Dupilumab [a monoclonal antibody blocking the shared receptor subunit for interleukin (IL)‐4 and IL‐13] is approved for the treatment of patients with inadequately controlled, moderate‐to‐severe AD. In 16‐week and 52‐week studies, dupilumab demonstrated a positive risk/benefit profile in moderate‐to‐severe AD. What does this study add? This study is the first comprehensive analysis of dupilumab laboratory safety data of the 16‐week SOLO 1 & 2 (pooled N = 1376) and 52‐week CHRONOS ( N = 740) trials, demonstrating an absence of clinically important changes in haematology, serum chemistry and urinalysis parameters in patients with moderate‐to‐severe AD treated with dupilumab. Our data support the use of dupilumab as a systemic treatment for the long‐term management of moderate‐to‐severe AD without routine laboratory monitoring in clinical practice. Abstract : Respond to this article